Концепт дом – house / home в значениях синонимов существительных home и house – имен концепта - Давыденко, И.В. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2012)
В статье раскрывается феномен лексической синонимии. Рассматриваются два подхода к исследованию синонимии: традиционный (семантический) и лингвокогнитивный (в свете теории прототипов и семейного сходства). Даются определения понятиям синонимия, синоним, категоризация, категория, прототип. Выявляются синонимы имен концепта ДОМ – HOUSE / HOME – house и home; выстраиваются синонимические ряды по линиям ЛСВ лексем house и home – имен концепта. У статті розкривається феномен лексичної синонімії. Розглядаються два підходи до дослідження синонімії: традиційний (семантичний) і лінгвокогнітивний (на базі теорії прототипів і сімейної подібності). Даються визначення поняттям синонімія, синонім, категоризація, категорія, прототип. Виявляються синоніми імен концепту ДІМ – HOUSE / HOME – house і home; формуються синонімічні ряди по лініях ЛСВ лексем house і home – імен концепту. The article focuses on the phenomenon of lexical synonymy. It represents two approaches to synonymy: traditional (semantic) and cognitive (based upon the theory of prototypes and family resemblance). The articles defines such concepts as synonymy, synonym, categorization, category and prototype; it reveals synonyms of the two names of the concept HOUSE / HOME – house and home; these synonyms are arranged according to the senses of lexemes house and home, which name the concept.
Keywords: категоризация; категория; концепт дом – house / home; прототип; синонимия; синоним; concept house / home; synonymy; synonym; categorization; category; prototype